Effects of elevated carbon dioxide on leaf gas exchange and growth of cork-oak (Quercus suber L) seedlings (Ann. For. Sci., 1996)
Leaf gas exchange and growth were determined on cork-oak (Quercus suber L) seedlings which were grown from acorns for periods of up to 4 months in greenhouses at ambient (350 μmol mol-1) and at elevated (700 μmol mor-1) concentrations of carbon dioxide. In well-watered conditions, daily maximum photosynthesis (15 μmol m-2 s -1) and stomatal conductance (440 mmol m-2 s-1) of plants grown and measured at 700 μmol mol-1 CO2 did not differ from those of plants grown and measured at 350 μmol mol-1. In conditions of moderate drought, net CO2 assimilation was at least twice as great in elevated CO2, but stomatal conductance was unchanged. Elevated CO2 affected total biomass production, the average increase being 76 and 97% at 3 and 4 months, respectively. Shoot biomass, root biomass, stem height and total leaf area were increased by elevated CO2. Root and stem ramification were also enhanced by elevated CO2, but no change in root/shoot ratio was observed.